مقترح إعداد موازنة تقليدية مختلطة في الوحدات الحكومية الخدمية دراسة تطبيقية في الجامعة المستنصرية وكلياتها (المجلة العراقية للعلوم الاقتصادية, 2018)
Was and is still planning budget traditional is adopted in estimating the expenses and revenues for the subsequent year and how to dispose of public funds and management in government service in Iraq , which is funded centrally by Iraqi of central bank and his branch after agreement the Ministry of finance according to his budgeting , and non- adoption application the rest of the budgets of other such as zero-budget and budget performance or programs & performance budget, despite the many criticisms that were directed to the traditional budget (budget items) by researchers and scholars over the years, the many negatives that accompany their application . According to researchers and scholars themselves that the reason for the continued adoption of the application of such budget in the management of public money and dispose of it, is the positives that accompany the application and the difficulty of making amendments of the lows and decrees, regulations and financial instructions issued by the legislative powers of the (lower house) or (Parliament) or issued by the authorities Executive of the council of Ministry or the so-called the (government ) or the chair and the respective ministers, especially the Ministry of Finance Technical Reference for government units, in addition to the lack of specialized staff for the application of those budget . With the aim of keeping two apples in one hand , the researcher is taking advantage positives produced by the applications , other planning budgets and introduce an element of accountability, additional stages of the budget and incorporated in the joints of the application of budget traditional through the design proposed model have called ( budget of traditional mixed ) , in order to increase effectiveness and efficiency of the budget currently applied in the government units. The study will be applied at the head of Mustansiriya University and their colleges.